2022
DOI: 10.1371/journal.pgen.1010412
|View full text |Cite
|
Sign up to set email alerts
|

Rdh54 stabilizes Rad51 at displacement loop intermediates to regulate genetic exchange between chromosomes

Abstract: Homologous recombination (HR) is a double-strand break DNA repair pathway that preserves chromosome structure. To repair damaged DNA, HR uses an intact donor DNA sequence located elsewhere in the genome. After the double-strand break is repaired, DNA sequence information can be transferred between donor and recipient DNA molecules through different mechanisms, including DNA crossovers that form between homologous chromosomes. Regulation of DNA sequence transfer is an important step in effectively completing HR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Based on prior studies identifying several disparate biochemical activities for RAD54 family translocases, we speculate that RAD-54.B might potentially function in multiple capacities at DSBR sites. For example, it might affect the structure of DSBR intermediates by modulating D-loop size or D-loop maturation, as proposed for yeast Rdh54/Tid1 (Keymakh et al, 2022;Shah et al, 2020), and/or it might modulate the activity of RAD-54.L in promoting RAD-51 removal. RAD-54.B functioning in such capacities at DSBR sites may underlie the modest difference in CO distribution observed in the rad-54.B mutant and the contribution of RAD-54.B to meiotic success in a rad-54.L partial loss-of-function background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior studies identifying several disparate biochemical activities for RAD54 family translocases, we speculate that RAD-54.B might potentially function in multiple capacities at DSBR sites. For example, it might affect the structure of DSBR intermediates by modulating D-loop size or D-loop maturation, as proposed for yeast Rdh54/Tid1 (Keymakh et al, 2022;Shah et al, 2020), and/or it might modulate the activity of RAD-54.L in promoting RAD-51 removal. RAD-54.B functioning in such capacities at DSBR sites may underlie the modest difference in CO distribution observed in the rad-54.B mutant and the contribution of RAD-54.B to meiotic success in a rad-54.L partial loss-of-function background.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional functions for S. cerevisiae Rdh54 and mammalian RAD54B have also been demonstrated in mitotically dividing cells where DMC1 is absent and RAD51 is the only recombinase. For example, yeast Rdh54 has been implicated in limiting the size of Rad51-mediated D-loop intermediates in vivo (Keymakh et al, 2022;Shah et al, 2020), and biochemical evidence indicates that the two RAD54 paralogs may occupy different sites on assembled presynaptic filaments (Crickard et al, 2020a), suggesting that both RAD54 paralogs may be deployed in different ways at the same DSBR site. Further, loss of either RAD54 paralog causes increased sensitivity to DNA damaging agents both in mouse embryonic stem cells and mice, with loss of both paralogs causing stronger sensitivity (Wesoly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This assay also contains markers to report on chromosome loss. We have previously used this assay and found that rad54 Δ /rad54 Δstrains are severely defective in this assay and result in limited recombination (27).…”
Section: Resultsmentioning
confidence: 99%
“…The WT strain used in this assay and the procedure for diploid formation are described here (27). The genotypes for modifying these strains can be found in Supplemental Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation